Total Plate Count of Broiler Meat at Various Market in Bekasi City in March 2021 - Firdausyi, Aulia Amatul; Estoepangestie, Agnes Theresia Soelih; Wibawati, Prima Ayu; Hamid, Iwan Sahrial; Solikhah, Tridiganita Intan; Prastiya, Ragil Angga (Universitas Airlangga, 2022)
Food-safety of broiler meat is important because broiler meat is a foodstuff that can be easily contaminated by biological hazard such as bacteria. This study aimed to determine the total plate count of broiler meat at various market in Bekasi City in March 2021. Amount of samples in this study were 40 samples of broiler meat from 10 markets, samples were taken purposively and each sample used 25 grams from Musculus pectoralis of broiler meat. Samples were examined using pour plate method of total plate count. The result showed that 80% (32 of 40 samples) were exceeded the TPC's limit. The highest value of TPC result was 3,7 í— 107 CFU/g from